Diffuse unilateral seminoma in a fighting rooster (Gallus gallus) - Ledesma, Nestor; Méndez, Adriana; González, José A.; Morales, Elizabeth (Brazilian Journal of Veterinary Pathology, 2018)
The aim of this study was to report a diffuse unilateral seminoma in a 4-year-old fighting rooster (Gallus gallus) by considering the anatomic, pathological and ultrastructural features. A significant decline in the viability of the bird's embryos was reported during the last year. The bird died with a marked abdominal distention. During necropsy, a firm ovoid neoplasm of approximately 9 cm long, 8 cm wide and 5 cm thick was found in the region adjacent to the pronephros, replacing the left testicle. The neoplasia was soft and encapsulated, and the cut surface showed extensive areas of haemorrhage interspersed with necrotic areas. Histologically, the neoplastic cells formed large mantles or cords with moderate and eosinophilic cytoplasm. The nuclei were pleomorphic, and some of them were central, while others were eccentric. Mitoses were scarce. Some important findings in the ultrastructural study were nuclei exhibited an elongated, electrodense, rope-like nucleoli and the presence of scarce intracytoplasmic glycogen. The anatomo-pathological and ultrastructural findings of the tumour were consistent with a seminoma. The ultrastructural study provided important support for the diagnosis, as other tumours were ruled out. The early diagnosis of malignant or benign testicular tumours in birds is the key for a timely treatment, as these tumours can metastasize or grow to such an extent that they compromise the lives of birds, as in the present case.